1972
DOI: 10.1136/bmj.3.5822.314
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Beclomethasone Dipropionate Aerosol and Prednisolone in Reversible Airways Obstruction

Abstract: in the patient's preference of the two treatment groups or in the number of times they used their bronchodilator aerosol, or in the forced expiratory volume in one second, vital capacity, or peak expfratory flow rate in the two treatment groups. The plasma cortisol levels when the patients were on the aerosol were much higher than when they were on prednisolone. The use of inhaled aerosol steroids seems to be preferable as it eliminates the usual complications of oral steroid therapy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
26
0

Year Published

1973
1973
2015
2015

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 95 publications
(28 citation statements)
references
References 20 publications
2
26
0
Order By: Relevance
“…It is our experience and that of others (Lal et al, 1972;Morrow Brown et al. 1972) that even after several vears of treatment oral steroids can be tailed off over a matter of several davs, provided that the patient is closely supervised and is instructed to report anv symntoms of acute adlrenal insufficiency.…”
Section: Discussionmentioning
confidence: 61%
See 2 more Smart Citations
“…It is our experience and that of others (Lal et al, 1972;Morrow Brown et al. 1972) that even after several vears of treatment oral steroids can be tailed off over a matter of several davs, provided that the patient is closely supervised and is instructed to report anv symntoms of acute adlrenal insufficiency.…”
Section: Discussionmentioning
confidence: 61%
“…Although control was not fully maintained in three of these, all the patients were able to stop continuous oral steroids. Successful transfer from oral prednisolone to inhaled beclomethasone was also achieved by Lal et al (1972) in a double-blind study of 38 patients without any deterioration in mean PEF. Their patients were, however, on lower maintenance steroid doses (up to 7 5 mg prednisolone daily) than ours and, although no individual figures of ventilatory function were given, nine patients were symptomatically worse after transfer.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…Morrow Brown et al (1972) found that 80% of 30 patients taking up to 10 mg prednisone daily could be transferred to BDA, whereas substitution was successful in only one of four patients taking a higher dose. Lal et al (1972) concluded that BDA 300 g daily was equivalent in effect to prednisone 7.5 mg daily. Clark (1972) considered that BDA 400 ,ug was approximately equivalent to prednisone 10 mg daily.…”
Section: Discussionmentioning
confidence: 99%
“…By the early 1970s, with the development of more modern ICS formulations, the promise of the pilot data from the Gelfand study was realized and expanded on by numerous other investigators [ 60 , 61 ]. For example, Lal et al reported on an inhaled preparation of beclomethasone that exhibited similar clinical effi cacy to systemic prednisolone [ 62 ]. Increasingly potent ICS formulations have led to dramatically improved control of asthma symptoms, with the localized dosing afforded through inhalation resulting in substantially fewer side effects and incidence of adrenal suppression in comparison to systemic GCs [ 24 , 63 ].…”
Section: Gcs In Asthma and Copd: Clinical Perspectivementioning
confidence: 99%